Muscle volume alterations in spastic muscles immediately following botulinum toxin type‐A treatment in children with cerebral palsy. (22nd June 2013) - Williams, Sîan A; Reid, Siobhan; Elliott, Catherine; Shipman, Peter; Valentine, Jane
Abstract : Aim: With evidence for an atrophic effect of botulinum toxin type A (BoNT‐A) documented in typically developing muscles, this study investigated the immediate morphological alterations of muscles in children with cerebral palsy (CP) after BoNT‐A treatment. Method: Fifteen children (10 males, five females; age range 5–11y, mean age 8y 5mo, SD 1y 10mo) with spastic diplegic CP [Gross Motor Function Classification System Levels I ( n =9) and II ( n =6)] receiving BoNT‐A injections for spasticity management were included. None of the children was a first‐time receiver of BoNT‐A. Magnetic resonance imaging and Mimics software assessed muscle volume, timed 2 weeks before and 5 weeks after injection. All participants received BoNT‐A bilaterally to the gastrocnemius muscle, and five participants also received BoNT‐A bilaterally to the medial hamstring muscles. Functional assessment measures used were the 6‐Minute Walk Test (6‐MWT), the Timed Up and Go (TUG) test, and hand‐held dynamometry. Results: Whilst total muscle group volume of the injected muscle group remained unchanged, a 4.47% decrease in the injected gastrocnemius muscle volume ( p =0.01) and a 3.96% increase in soleus muscle volume ( p =0.02) was evident following BoNT‐A. There were no statistically significant changes in function after BoNT‐A as assessed by the TUG. There was also no statistically significant change in distance covered in the 6‐MWT. Muscle strength, as assessed using hand‐held dynamometry was also not statistically different after BoNT‐A treatment. Interpretation: Muscle volume decreases were observed in the injected muscle (gastrocnemius), with synergistic muscle hypertrophy that appeared to compensate for this decrement. The 4% to 5% decrease in the volume of BoNT‐A injected muscles are not dramatic in comparison to reports in recent animal studies, and are a positive indication for BoNT‐A, particularly as it also did not negatively alter function. Abstract : This article is commented on by Hastings‐Ison and Graham on pages778–779 of this issue.